THU0221 Osteonecrosis and hiv infection: report of eleven cases. (1st June 2001) - Valls-Roc, M; Ortiz-Santamaria, V; Olive, A; Cervantes, M; Gratacos, J; Sirera, G; Tural, C; Negredo, E; Tena, X; Clotet, B
Abstract : Background: A vascular necrosi (AVN) has been described in the setting of HIV infection. No epidemiological studies to determine the higher incidence of AVN in HIV+ patients are available. Protease inhibitor containing regimens (PI-CR) have been considered an additional risk factor for developing AVN. Objectives: To report the clinical findings of 11 HIV + patients with AVN. Methods: Retrospective review of clinical and radiological charts of 11 patients diagnosed of AVN. Results: Eleven patients were diagnosed of having AVN: Eight male and three female. The mean age was 27.6 years (23–32). The risk factors for HIV infection was as follows: 8 IDU, 3 HMX. Nine patients had had at least one opportunistic infection with a mean time of 30.5 months before the diagnosis of the AVN (12–108). The mean CD4 + and pVL at AVN were 328.9 cel/mm3 (73–900) and 14.964 copies/ml (6 of them had undetectable levels: <200 copies/ml) respectively. Mean CD4 + nadir was 53 cel/mm3. The mean time on PI-CR before the AVN was 19.4 months (2 patients were naïve for PIs before AVN). MRI showed a bilateral femoral head involvement in 9 patients, 2 of them with additional humeral and knee involvement. Other risk factor related to the development of AVN were evaluated: 6 patients had received corticosteroids prior to the AVN, hyperlipidaemia secondary to PI-CR was reported only in 2 patients. Six months before the AVN, salmonella typhymurium bacteriemia was documented in 2 patients. Conclusion: Despite the higher incidence of AVN reported in HAART era, epidemiological studies should be conducted in order to establish the role of PIs in its aetiology. Other risk factor such as corticoesteroids use related to AVN, should be assessed in HIV+ patients with AVN.